Immunoregulation in disseminated histoplasmosis: characterization of the surface phenotype of splenic suppressor T lymphocytes. - Watson, S R (1982)
C57BL/6 and C3H/HeJ mice were infected intravenously with 6 X 10(5) yeast-phase Histoplasma capsulatum organisms. After 1 week, splenocytes from both mouse strains showed diminished antibody responses to sheep erythrocytes in vitro; these cells also were able to suppress the response of normal syngeneic cells. Passage of splenocytes from infected mice through a nylon wool column yielded a population enriched for T cells that exerted suppressor activity, although to a smaller extent than did unfractionated cells. Treatment of the T-cell-enriched population from both strains of mice with either anti-Thy 1.2 or anti-Ly 2 and complement resulted in a loss of this immunosuppressive ability. In addition, anti-I-Jk antiserum was effective in ablating the suppressive effect of C3H/HeJ nylon wool-passed spleen cells. The conclusion drawn from these experiments is that the T cells from H. capsulatum-infected animals which are capable of modulating the in vitro plaque-forming cell response to sheep erythrocytes bear Ly 2 and I-J determinants on their surfaces.